2nd IET International Conference on Intelligent Environments (IE 06) 2006
DOI: 10.1049/cp:20060676
|View full text |Cite
|
Sign up to set email alerts
|

Review of technology solutions for knowledge management

Abstract: Abstract:The present paper focuses on Knowledge Management (KM) as a new managerial discipline emerging in the last few years of the 20 th century. The main emphasis of the paper is on the technological solutions applied in the organizations at different stages of the KM life cycle. It makes a classification of the types of technologies described in the theory and practice based on the main KM processes. Finally, are presented survey data on the real application of various knowledge management technologies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Antonova, Gourova, and Nikolov () reviewed technological solutions for KM. On the basis of the main KM processes, they presented a classification of different facilitating technological solutions described in theory and practice.…”
Section: Background: Past Predictions On Future Research Themesmentioning
confidence: 99%
See 3 more Smart Citations
“…Antonova, Gourova, and Nikolov () reviewed technological solutions for KM. On the basis of the main KM processes, they presented a classification of different facilitating technological solutions described in theory and practice.…”
Section: Background: Past Predictions On Future Research Themesmentioning
confidence: 99%
“…On the basis of the main KM processes, they presented a classification of different facilitating technological solutions described in theory and practice. Later, using data from a survey conducted by KPMG (KPMG, ), Antonova et al () demonstrated that technologies play a vital role in KM processes. However, they emphasized the need for KM implementation to focus in the first instance on human and organizational issues and not technology.…”
Section: Background: Past Predictions On Future Research Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a knowledge management system must be a sociotechnical system as a whole which comprises the knowledge itself (the intellectual capital of the organisation), organisational attributes (intangibles such as trusting culture), policies and procedures, as well as some form of electronic storage and retrieval systems." Different ways of classifying knowledge management technologies are utilised in the literature and Antonova, Gourova et al [25] categorised technological solutions according to the following knowledge management processes: (1) generation of knowledge, (2) storing, codification and representation of knowledge, (3) knowledge transformation and knowledge use and (4) transfer, sharing, retrieval, access and searching of knowledge.…”
Section: The Knowledge In Knowledge Managementmentioning
confidence: 99%